A posição da coluna lombar altera o padrão de recrutamento dos músculos abdominais em pacientes portadores de dor lombar crônica e indivíduos saudáveis? - Rafael Zambelli de Almeida Pinto (2008)
Non-specific chronic low back pain (CLBP) is a prevalent condition with significant economic impact and personal costs. Patients with CLBP show an altered pattern of recruitment of the deep abdominal muscles. Intervention for this population aimed at retraining these muscles is usually prescribed based on evidence from randomized controlled trials. Among all the strategies used within this approach, the control of neutral position of the lumbar spine has been clinically associated with a reduction in pain and disability in CLBP. This position is defined clinically with the subject seated under the ischial tuberosities with the manubrium in alignment with the anterior aspect of the pelvis, involving the maintenance of a neutral pelvic tilt, lumbar e cervical lordosis and smooth transition to thoracic kyphosis. Despite the efficacy of this program, it is not known if neutral position of the lumbar spine can improve recruitment of the deep abdominal muscles. The aim of the present study was to compare the abdominal muscle recruitment (measured as a change in thickness with ultrasound imaging) between people with and without CLBP in two different lumbar postures, neutral lumbar posture (NLP) and slump lumbar posture (SLP), while performing an isometric leg task. Material and methods: The pattern of abdominal muscle recruitment of 30 subjects with CLBP and 30 controls were tested in 2 conditions while performing an isometric leg task. These conditions, NLP and SLP, were used in order to simulate the lumbar curvature found in upright and slump sitting. The recruitment pattern of transversus abdominis (TrA), obliquus internus (OI), and obliqus externus (OE) muscles were assessed by ultrasonography imaging. Results: In controls, NLP showed significantly greater thickness in TrA (P < 0.001) and OE (P = 0.027) compared to SLP. In CLBP, no significant differences were found between the groups. Conclusions: In controls, lumbar curvature in a more neutral posture seems to preferentially recruit deep abdominal stabilizing muscles compared with slump or fully flexed lumbar curvature. However, in CLBP neutral lumbar curvature alone is not capable of improving the recruitment of these muscles and other mechanisms might be associated with the positive clinical results of interventions aimed at training the deep muscles of the spine.